Tension and pulse at Intubation before and after 5 minutes on Neurology Patients with General Anaesthesia - Donsu, Jenita Doli Tine; Herawati, Lucky; Palestin, Bondan; Pratiwi, Reza Dwi; Hutasoit, Mastha (Riset Informasi Kesehatan, 2025)
Background: General anesthesia is still the best choice for neurosurgery, even it must be maintained so that the airway remains open. Airway management measures that can be carried out in several ways include intubation using laryngoscopy. There may be an increase in the hemodynamic response, namely blood pressure and pulse rate starting from 5 seconds after intubation. However, it is still being debated by experts. The aim of this study was to determine blood pressure and pulse frequency after being given Fentanyl and after the 5th minute of intubation in neurosurgical patients under general anesthesia. Method: An observational research design, 30 neurosurgical patients using fentanyl 2 mcg/kg BW and intubation techniques. The variables measured were blood pressure and pulse frequency after being given Fentanyl and after 5 minutes of intubation. The instruments used were an intra-anesthetic Hemodynamic Observation Sheet, a watch, and a bedside monitor. Data was analyzed using the independent T-test with a level of confidence of 95%. Results: The results showed that there was an increase in the average Systolic blood pressure (p-value 0.009) and pulse frequency (before intubation) and after intubation at the 5th minute (p-value 0,000). Conclusion: The study can trigger anesthesia experts to look forward to this problem appropriately